Identification of mutations allowing Natural Resistance Associated Macrophage Proteins (NRAMP) to discriminate against cadmium. (21st July 2015) - Pottier, Mathieu; Oomen, Ronald; Picco, Cristiana; Giraudat, Jérôme; Scholz‐Starke, Joachim; Richaud, Pierre; Carpaneto, Armando; Thomine, Sébastien
Summary Each essential transition metal plays a specific role in metabolic processes and has to be selectively transported. Living organisms need to discriminate between essential and non‐essential metals such as cadmium (Cd2+), which is highly toxic. However, transporters of the natural resistance‐associated macrophage protein (NRAMP) family, which are involved in metal uptake and homeostasis, generally display poor selectivity towards divalent metal cations. In the present study we used a unique combination of yeast‐based selection, electrophysiology on Xenopus oocytes and plant phenotyping to identify and characterize mutations that allow plant and mammalian NRAMP transporters to discriminate between their metal substrates. We took advantage of the increased Cd2+ sensitivity of yeast expressing AtNRAMP4 to select mutations that decrease Cd2+ sensitivity while maintaining the ability of AtNRAMP4 to transport Fe2+ in a population of randomly mutagenized AtNRAMP4 cDNAs. The selection identified mutations in three residues. Among the selected mutations, several affect Zn2+ transport, whereas only one, E401K, impairs Mn2+ transport by AtNRAMP4. Introduction of the mutation F413I, located in a highly conserved domain, into the mammalian DMT1 transporter indicated that the importance of this residue in metal selectivity is conserved among NRAMP transporters from plant and animal kingdoms. Analyses of overexpressing plants showed that AtNRAMP4 affects the accumulation of metals in roots. Interestingly, the mutations selectively modify Cd2+ and Zn2+ accumulation without affecting Fe transport mediated by NRAMP4 in planta. This knowledge may be applicable for limiting Cd2+ transport by other NRAMP transporters from animals or plants.